THE EFFECT OF HEMODIAFILTRATION ON BIOCHEMICAL PARAMETERS IN END STAGE KIDNEY DISEASE PATIENTS AT THE IRAQI CENTER OF HEMODIALYSIS - Ahmad Daher Mohsen; Mohammed Hannon Al-Sodani (Western European Studies, 2024)
Chronic kidney disease is a chronic ailment that profoundly impacts overall health and quality of life. As kidney function deteriorates, the buildup of toxins and electrolyte imbalances necessitates the use of renal replacement therapy to maintain physiological homeostasis in patients. The predominant options for substitute renal function include hemodialysis and hemodiafiltration, which have become the primary methods for managing end-stage renal disease. The primary objective of hemodialysis is to enhance patient survival, elevate quality of life, and mitigate problems associated with the procedure. To achieve this objective, dialysis prescriptions were formulated, augmenting the biocompatibility of dialysis filters and boosting the efficacy of medium-sized molecule toxin elimination via improved diffusion and convection. Hemodiafiltration with a large convective volume significantly reduces morbidity and mortality in patients undergoing hemodialysis
Keywords: hemodialysis; augmenting; methods